Formulasi dan Karakterisasi Nanoserum Kombinasi Ekstrak Wortel (Daucus carota L.) dan Astaxanthin sebagai Antioksidan - Tiara Bella Pratiwi; Arif Budi Setianto; Nuri Ari Efiana; Sri Mulyaningsih (Jurnal Ilmiah Farmako Bahari, 2026)
Lipophilic antioxidants such as β-carotene and astaxanthin have strong potential to protect the skin against oxidative stress; however, their topical application is limited by low stability and insufficient skin penetration. This study aimed to formulate and evaluate the physical characteristics, stability, and antioxidant activity of a nanoserum combining carrot extract (Daucus carota L.) and astaxanthin. Carrot extract was obtained by maceration using 96% ethanol and formulated into a nanoemulsion-based serum containing three extract concentrations: 5% (F1), 10% (F2), and 15% (F3), with 1% astaxanthin. The formulations were evaluated for organoleptic properties, particle size, polydispersity index (PDI), zeta potential, pH, viscosity, and adhesiveness. Stability was observed up to 6 days, while antioxidant activity was determined using ABTS and FRAP assays. All formulations exhibited nanoscale particle sizes with good homogeneity (PDI <0.5) and negative zp (<-30 mV), indicating stable dispersions. Formula F2 showed the most favorable characteristics, with a particle size of 39.21 ± 0.32 nm, PDI of 0.25 ± 0.02, and zeta potential of −33.66 ± 0.27 mV, along with suitable pH and viscosity for topical application. F2 demonstrated very strong antioxidant activity, with IC₅₀ values of 9.04 ± 0.19 ppm (ABTS) and 16.78 ± 0.04 ppm (FRAP), which remained in the strong category after storage. In conclusion, the carrot extract–astaxanthin nanoserum was successfully developed, with F2 identified as the optimal formulation.